Salinity controlling enhanced high-salinity pickle wastewater treatment coupling with high-value fatty acid production by Dunaliella salina - Hu, Hao; Wu, Bang-Lei; Wei, Dong; Yu, Li; Li, Wei-Hua; Zhu, Shu-Guang (Journal of cleaner production, 2024)
The use of salt-tolerant microalgae to treat high-salinity pickle wastewater and produce harvest high-value compounds is an economical and eco-friendly production strategy. However, the effects of salinity gradient on the removal of soluble pollutants and high-value compound production have rarely been systematically evaluated. The objective of this study was to evaluate the efficiency of salt-tolerant microalgae in removing soluble pollutants from high-salinity pickle wastewater, and the output of high value-added products (oleic acid and linolenic acid) by controlling the salinity. Taking a salt-tolerant microalgae Dunaliella salina as a subject, seven salinity gradients from 23.7 to 130 g/L salinity were set to treat high-salinity pickle wastewater. The results showed ammonia nitrogen and nitrate nitrogen had the maximum removal of 97% and 96% respectively, and the maximum average removal rate of chemical oxygen demand reached 290.54 ± 3.55 mg L-1 d-1, simultaneously oleic acid and linolenic acid production reached the peak, in 30 g/L salinity, which reflected that the best coupling effect was achieved at this salinity. Additionally, accumulation of oleic acid and linolenic acid at different salinity gradients was briefly analyzed by their pathways. This study is expected to promote not only high-salinity pickle wastewater treatment but also resource utilization by microalgae. [Display omitted] •30 g/L NaCl improved soluble pollutant removal.•The production of oleic acid and linolenic acid reached the highest at 30 g/L NaCl.•30 g/L NaCl is the best salinity for coupling effect.•Dunaliella salina is positive for chemical oxygen demand removal.